Reformasi pembelajaran era covid-19: Pembelajaran online berbasis masalah dalam meningkatkan kemampuan berpikir kreatif siswa SMP - Asri Ode Samura; Mubin Noho (Mahesa Research Center, 2022)
This research was conducted online using Zoom cloud meetings and studied and analyzed the improvement of junior high school students' creative thinking skills through problem-based and conventional learning. This study uses a quantitative method designed with a nonequivalent control group experimental pattern. The sample is 75 people, not taken randomly from two different classes. One class is problem-based learning, and another is conventional learning. Data collection was carried out using tests, namely the pretest and the posttest. They measure the increase in creative thinking skills using normalized N-Gain. The data were analyzed using an independent sample t-test. The study found that the problem-based learning model was more influential than conventional learning in improving junior high school students' mathematical creative thinking skills. Problem-based and conventional learning can improve junior high school students' mathematical and creative thinking skills.